Dental education: Lecture versus flipped and spaced learning - Shivani Kohli; Ashwin Kumar Sukumar; Cheah Tze Zhen; Andrew Sim Lim Yew; Alvena Ann Gomez (Wolters Kluwer Medknow Publications, 2019)
Background: Even though there are diverse varieties of teaching methods to motivate and educate students, not many are used in dental institutions, where most rely only on traditional lectures. Hence, the objective of this study was to compare traditional lectures with newer teaching methods, specifically the flipped classroom and spaced learning method. Materials and Methods: In this prospective cohort study Students were randomized to one of the teaching methods, and their short-term (immediately after teaching) and long-term (i.e., 6 months later) knowledge retention was assessed through multiple choice questions, followed by students feedback which was obtained using Trierer Inventar zur Lehrevaluation questionnaire. P≤ 0.05 was considered statistically significant. Results: For short-term learning gains, spaced learning group (165.85) showed highest mean scores, followed by the traditional lecture group (163.70) and flipped classroom group (153.25).P value acquired through the Kruskal-Wallis ANOVA was statistically significant (0.003). For long-term knowledge retention, traditional lecture group has highest mean scores (147.50), followed by spaced learning group (146.90) and flipped classroom group (145.05) with no significant difference (P = 0.657). Conclusion: Spaced learning methodology was better than the traditional lecture method and the flipped classroom concerning knowledge gains when measured immediately after the application of learning method. For long-term knowledge retention, both the flipped classroom and spaced learning teaching methods were comparable to the traditional lecture method.